2014
DOI: 10.1111/bcpt.12334
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anti‐Emetic Efficacy of 5‐HT3 Receptor Antagonists in Cancer Patients with Genetic Polymorphisms of ABCB1 (MDR1) Drug Transporter

Abstract: Chemotherapy-induced nausea and vomiting (CINV) remains a major adverse effect decreasing quality of life in patients with cancer. Genetic variations among patients may be responsible for part of the lack of efficacy of anti-emetic drugs. The aim of this study was to investigate how the genetic variants of the drug transporter ABCB1 (MDR1) gene affect anti-emetic treatment with 5-HT3 receptor antagonists. Patients (n = 239) receiving moderately or highly emetogenic chemotherapy and ondansetron or granisetron w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 26 publications
1
61
1
Order By: Relevance
“…In a previous study of patients with cancer using antiemetic drugs, Zoto et al 27 have reported that TT-TT-TT haplotype frequency was 13% in a Turkish sample of 239 patients. Hence, the nonexistence of the ABCB1 TT-TT-TT haplotype we found in the agranulocytosis group is unexpected and might be a distinguishing factor in the development of CAA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a previous study of patients with cancer using antiemetic drugs, Zoto et al 27 have reported that TT-TT-TT haplotype frequency was 13% in a Turkish sample of 239 patients. Hence, the nonexistence of the ABCB1 TT-TT-TT haplotype we found in the agranulocytosis group is unexpected and might be a distinguishing factor in the development of CAA.…”
Section: Discussionmentioning
confidence: 96%
“…The forward and reverse primers (Alpha DNA, Montreal, Quebec, Canada) and PCR conditions were used as presented in previous studies. 26,27 The PCR reactions were performed in a total volume of 50 μL containing 100-to 200-ng DNA, 100 μM of each deoxynucleotides, 0.2 μM of each primers for G2677T/A, C3435T polymorphisms, and 0.1 μM of each primers for C1236T polymorphism, 2.5 U of Taq polymerase (New England Biolabs GmbH, Frankfurt, Germany), and 0.75 μL of dimethyl sulfoxide for only C1236T detection. Amplification was performed by using a thermal cycler (Applied Biosystems 2720, Waltham, Mass); restriction enzymes (New England Biolabs GmbH), corresponding fragment sizes for each allele, and incubation conditions have been described previously.…”
Section: Sample Collection and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Moreover, there are several reports showing that polymorphisms of the adenosine triphosphate-binding cassette subfamily B member 1 (ABCB1) transporter protein are also associated with CINV and postoperative nausea and vomiting. [16][17][18][19][20] However, these investigations were on the basis of first-generation 5-HT 3 receptor antagonists, such as ondansetron and granisetron, without neurokinin-1 receptor antagonist, and there are conflicting reports on the effects of ABCB1 polymorphisms. Furthermore, in these studies, the use of antiemetic medications, such as dexamethasone, was not in accordance with the antiemetic guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications have shown that the haplotype (TT/TT) at positions 3435 and 2677 of the ABCB1 gene was associated with poorer treatment outcomes in patients with epilepsy and a required higher methadone dose in patients with heroin dependence . On the contrary, other publications have found a higher antiemetic response in patients that carry the genotype TT at positions 3435 and/or 2677 of the ABCB1 gene . Finally, ABCB1 activity increases during pregnancy; therefore drugs that are substrates for ABCB1 may become even less effective during pregnancy in patients that carry ABCB1 SNPs associated with reduced control of emesis.…”
Section: Discussionmentioning
confidence: 99%